Combined Use of Excimer Laser and High-Speed Rotational Atherectomy to Overcome a Severely Calcified Lesion in Endovascular Therapy - Keisuke Nakabayashi; Shinya Hata; Nobuhito Kaneko; Akihiro Matsui; Kazuhiko Tanaka; Hiroshi Ando; Minoru Shimizu (Case Reports in Vascular Medicine)
Although endovascular therapy (EVT) is commonly used in treatment of peripheral artery disease (PAD), severely calcified lesions pose a challenge, in spite of the technical advancement. In this report, we discuss the case of a 74-year-old male with coronary artery disease and end-stage renal disease who presented at our institution with bilateral intermittent claudication. Angiography showed chronic total occlusion (CTO) of the right superficial femoral arteries (SFA). Because the bilateral external iliac arteries demonstrated moderate stenosis, we performed endovascular therapy on the right SFA-CTO using a contralateral approach. With the antegrade wire progressing into the subintimal space, direct distal-SFA puncture was performed and wire externalization was established. However, no devices (minimal balloon, microcatheter, or Crosser system) were able to pass the lesion in antegrade or retrograde manner, even though the child catheter support or needle cracking technique from outside/inside was applied. Therefore, we used a combination of an excimer laser and high-speed rotational atherectomy to overcome the severely calcified lesion. First, the excimer laser catheter (Turbo Elite 0.9 mm) ablated the entry to the CTO; however, it did not pass through completely. Thereafter, the thin microcatheter (Caravel) succeeded in crossing the CTO in an antegrade manner using the BAlloon Deployment using FORcible Manner (BADFORM) technique. After wire-exchange to the Rota-wire, rotational atherectomy (RotaLink Plus 1.5 mm) passed through the CTO. Subsequently, we could dilate the CTO lesion with a conventional balloon followed by bare metal stent deployment. The right ankle-brachial index of the patient improved from being unmeasurable to 0.79, and the intermittent claudication disappeared. This combination therapy, described as the “RASER” technique in coronary section, is accepted for reimbursement. However, these devices in EVT section are considered off-label use in Japan. Therefore, we have to refrain from frequent use of this strategy; however, this method provides an option for severely calcified lesions.